2010
DOI: 10.1371/journal.pone.0015716
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Availability Controls TRB3 Transcription in Liver through the GCN2/eIF2α/ATF4 Pathway

Abstract: In mammals, plasma amino acid concentrations are markedly affected by dietary or pathological conditions. It has been well established that amino acids are involved in the control of gene expression. Up to now, all the information concerning the molecular mechanisms involved in the regulation of gene transcription by amino acid availability has been obtained in cultured cell lines. The present study aims to investigate the mechanisms involved in transcriptional activation of the TRB3 gene following amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 51 publications
(95 reference statements)
2
57
0
Order By: Relevance
“…TRB3, a known direct target of ATF4 (25,29,30), is induced by ethanol treatment in cells (33,42) and livers, as shown in our current study. However, the role of TRB3 in alcoholic liver steatosis has not been studied previously.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…TRB3, a known direct target of ATF4 (25,29,30), is induced by ethanol treatment in cells (33,42) and livers, as shown in our current study. However, the role of TRB3 in alcoholic liver steatosis has not been studied previously.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, ATF4 regulates AMPK activity via Tribbles homolog 3 (TRB3), a direct target of ATF4 (25), which could bind directly to AMPK and suppress its phosphorylation. Taken together, our results identify the ATF4-TRB3-AMPK axis as a novel pathway responsible for ethanol-induced liver steatosis.…”
mentioning
confidence: 99%
“…Following activation of the AAR, increased acetylation of both H3 and H4, in parallel with a rapid increase in ATF4 binding, has been observed at the ASNS and ATF3 proximal promoters (35,39). Carraro et al observed that AARinduction led to an increase in H2B, H3, and H4 acetylation levels at the TRB3 CARE site (59). The sodium-dependent neutral amino acid transporter 2 (SNAT2) gene has an intronic CARE enhancer (60).…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid deficiency triggers a series of signal transduction pathways collectively referred to as the amino acid response (AAR). A number of genes critical to the AAR have been identified (6,21), but the mechanistic details of their transcriptional control are not fully understood. The general control nonderepressible 2 (GCN2) kinase acts as an sensor for amino acid levels by binding uncharged transfer tRNA, which leads to phosphorylation of the alpha subunit of the translation initiation factor eIF2 and increased translation of the activating transcription factor 4 (ATF4).…”
mentioning
confidence: 99%